Redefining a lost urban waterway application of blue- green network strategy in the redevelopment of the Estero De Balete - Llaban, Rafael Luis F. (College of Architecture, University of the Philippines Diliman, 2023)
Urban rivers are a common sight in cities around the world, as human settlements historically develop along bodies of water (Pante, 2019). The rapid urbanization of the past century has seen many rivers in major cities covered up and restricted to underground culverts that constrict its flow and their ecological functions severely degraded (Shahady, 2021; Wilson, 2016). Urban waterways however are also part of a larger system of their watershed and thus urbanization away from the channel also affects the health of urban river ecosystems (Platt, 2006). The Blue-Green network strategy is an urban and regional planning approach borne of modern understanding of the relationship of the built environment and nature (Planning a Blue-Green City, 2017; Wilson, 2016). The Blue-green network strategy, along with related sustainable landscape design principles are applied to a proposed redevelopment of the Estero de Balete in Manila. The study looks to draw from the best environmental management practices outlined therein and apply it to the Philippine context in the chosen site. The chosen site is a channelized waterway and minor tributary of the Pasig river located in the historic district of Ermita. Initial inspection of an 1898 map of Manila and its suburbs, shows that the Estero historically covered approximately 2.3 kilometers in its longest stretch, but currently only 700 meters of open-air waterway remains. Its historical extents pass through areas of cultural significance, as well as civil and academic institutions. This thesis seeks to propose a design of a restored open-air watercourse of the Estero de Balete with a greenway development that provides social and ecological benefits to the area. To achieve this goal the objectives of the proposal are: (1) Document the boundaries of the whole Estero de Balete from natural, legal, and historical perspectives (2) Gather data on the study area relevant to the river morphology of the Estero de Balete and the urban ecology of its surrounding area. (3) Identify methods of Greenway development and Urban River Rehabilitation that are appropriate in the context of the given site. (4) Consult stakeholders in the study area to determine their current perceptions of the Estero and preferences for a redevelopment. (5) Synthesize the research findings into a proposed design for a Redefining a Lost Urban Waterway, Application of Blue-Green Network revitalized Estero de Balete. The approaches and philosophy of the Blue-Green Network strategy will inform the design process. The study will achieve the goals outlined above by accessing primary data (surveys, interviews, site inspection) and secondary data (Case studies, Government documents, Maps) to inform the design process. Data analysis will take the form of a thematic analysis to assess the themes in the data gathered that will be translated into the design solution. It is hypothesized that the goal of an integrated blueway development of the estero de balete using the blue-green network strategy will bring greater social and environmental benefits to the surrounding area than the current layout of the urban environment. This was determined by a comparative analysis of the impacts of the proposal to other case study developments with similar features